Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Wolkite University - International Livestock Research Institute; Wolkite University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MoU) between the International Livestock Research Institute (ILRI) and Wolkite University. On April 6, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Faris Delil Yesuf, President of Wolkite University.